Opportunities and challenges of leveraging COVID-19 vaccine innovation and technologies for developing sustainable vaccine manufacturing capabilities in Africa - (:unkn) unknown (My University, 2023)
The COVID-19 pandemic heralded unprecedented resource mobilisation and global scientific collaboration to rapidly develop effective vaccines. Regrettably, vaccine distribution has been inequitable, particularly in Africa where manufacturing capacity remains nominal. To address this, several initiatives are underway to develop and manufacture COVID-19 vaccines in Africa. Nevertheless, diminishing demand for COVID-19 vaccines, the cost competitiveness of producing goods locally, intellectual property rights issues, and complex regulatory environments among other challenges can undermine these ventures. We outline how extending COVID-19 vaccine manufacturing in Africa to include diverse products, multiple vaccine platforms, and advanced delivery systems will ensure sustainability. Possible models, including leveraging public–academic–private partnerships to enhance success of vaccine manufacturing capacity in Africa are also discussed. Intensifying research in vaccine discovery on the continent could yield vaccines that further bolster sustainability of local production, ensuring greater pandemic preparedness in resource-constrained environments, and long-term health systems security.
Keywords: African Research